2012
DOI: 10.1159/000336731
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Interneuron Dysfunction in Schizophrenia

Abstract: Schizophrenia is a debilitating neurodevelopmental disorder affecting approximately 1% of the population and imposing a significant burden on society. One of the most replicated and well-established postmortem findings is a deficit in the expression of the gene encoding the 67-kDa isoform of glutamic acid decarboxylase (GAD67), the primary GABA-producing enzyme in the brain. GAD67 is expressed in various classes of interneurons, with vastly different morphological, molecular, and physiological properties. Impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 235 publications
(139 reference statements)
0
12
0
Order By: Relevance
“…Adult mice with GAD1 gene expression deficits in restricted interneuron populations have distinct molecular and behavioral dysfunction depending on the affected cell type Kvitsiani et al, 2013;Schmidt et al, 2013). These data provide functional context to postmortem studies that consistently implicate diverse interneuron cell types in schizophrenia (Hashimoto et al, 2003(Hashimoto et al, , 2008aHoftman et al, 2013;Iritani et al, 2000;Kuromitsu et al, 2001;Maldonado-Aviles et al, 2009;Mellios et al, 2009;Morris et al, 2008;Volk et al, 2012) and suggest that GABAergic gene expression deficits seen in post-mortem studies of patients with schizophrenia actively contribute to important aspects of brain development and behavior (Lewis et al, 2005;Marin, 2012;Schmidt and Mirnics, 2012).…”
Section: Gene Effects Converge Onto Gaba System Developmentmentioning
confidence: 79%
See 2 more Smart Citations
“…Adult mice with GAD1 gene expression deficits in restricted interneuron populations have distinct molecular and behavioral dysfunction depending on the affected cell type Kvitsiani et al, 2013;Schmidt et al, 2013). These data provide functional context to postmortem studies that consistently implicate diverse interneuron cell types in schizophrenia (Hashimoto et al, 2003(Hashimoto et al, , 2008aHoftman et al, 2013;Iritani et al, 2000;Kuromitsu et al, 2001;Maldonado-Aviles et al, 2009;Mellios et al, 2009;Morris et al, 2008;Volk et al, 2012) and suggest that GABAergic gene expression deficits seen in post-mortem studies of patients with schizophrenia actively contribute to important aspects of brain development and behavior (Lewis et al, 2005;Marin, 2012;Schmidt and Mirnics, 2012).…”
Section: Gene Effects Converge Onto Gaba System Developmentmentioning
confidence: 79%
“…Since the initial description of the neurodevelopmental hypothesis of schizophrenia, data from epidemiological, clinical, post-mortem, and animal model studies continue to support and extend its premise (Brandon and Sawa, 2011;Brown, 2011;Horvath and Mirnics, 2014a, b;Lewis and Levitt, 2002;Lewis and Mirnics, 2006;Michel et al, 2012;Mirnics et al, 2000Mirnics et al, , 2001bMirnics et al, , 2006Mirnics and Lewis, 2001a;Rapoport et al, 2012;Schmidt and Mirnics, 2012). Concurrently, GABAergic dysfunction has become recognized as a hallmark feature of the disorder.…”
Section: Future Research Directionsmentioning
confidence: 96%
See 1 more Smart Citation
“…ketamine, MK-801) in rodents, as this model has shown changes in PV expression comparable to those seen in human postmortem tissue, in addition to alterations in cognitive performance [for reviews, see [33,34,35]]. However, these studies have revealed conflicting results with regard to whether the NMDA hypofunction model produces changes in PV immunoreactivity quantified by either immunohistochemical staining and/or protein assays.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, molecular alterations in PV interneurons (PVI) have been reported in prefrontal cortex and other cortical areas of SCZ subjects (Fung, Webster, Sivagnanasundaram, Duncan, Elashoff, and Weickert, 2010; Mellios, Huang, Baker, Galdzicka, Ginns, and Akbarian, 2009; Volk and Lewis, 2013), including downregulated expression of GABA synthesis enzyme GAD1/GAD67 (Hashimoto, Volk, Eggan, Mirnics, Pierri, Sun, Sampson, and Lewis, 2003), potassium channel subunits (Georgiev, Arion, Enwright, Kikuchi, Minabe, Corradi, Lewis, and Hashimoto, 2014) and transcription factors (Volk, Matsubara, Li, Sengupta, Georgiev, Minabe, Sampson, Hashimoto, and Lewis, 2012a), among various others (Volk, Chitrapu, Edelson, and Lewis, 2014). In addition to PV, low-threshold spiking SST+ neurons also demonstrate altered gene expression in SCZ cortex and hippocampus (Akbarian and Huang, 2006; Fung, Fillman, Webster, and Shannon Weickert, 2014; Fung et al, 2010; Konradi, Yang, Zimmerman, Lohmann, Gresch, Pantazopoulos, Berretta, and Heckers, 2011; Mellios et al, 2009; Schmidt and Mirnics, 2012). According to some estimates, up to 30–40% of subjects with schizophrenia show robust decreases in expression in a subset of RNAs specifically expressed in GABA neurons (Volk, Matsubara, Li, Sengupta, Georgiev, Minabe, Sampson, Hashimoto, and Lewis, 2012b).…”
Section: Introductionmentioning
confidence: 99%